Pendidikan Perkoperasian dan Kelembagaan Koperasi bagi Anggota Baru dan Calon Anggota KKBSK (Koperasi Guru Karyawan SMK Koperasi) di Yogyakarta - Rosti Setiawati (LPPM Universitas Koperasi Indonesia, 2023)
One of the cooperative principles is cooperative education, including education for cooperative members, meaning that a member of a cooperative must have knowledge and understanding of cooperatives, what are the rights and obligations of a cooperative member, so that cooperative members can actively participate in cooperatives. Cooperative education is very important for members because it can foster a sense of belonging to cooperatives as business entities owned by members and members want to make transactions at cooperatives with a position as customers of cooperatives in meeting their needs. Members have knowledge about the difference between being a member and not being a member of a Cooperative, as well as what benefits members can get by joining a Cooperative. The progress or success of a Cooperative business depends on theparticipation of members because the Cooperative philosophy is from members, by members, and for members. So that cooperative members really need an understanding of the basis of cooperatives and cooperative institutions. This Cooperative Education Training is a collaboration between the Indonesian Cooperative University and the Yogyakarta-Yapendikopyo Cooperative Vocational School (Yogyakarta Cooperative Education Foundation). The training method is carried out using an education approach for adults, starting with the presentation of material through lectures followed by a question and answer session and discussion. The training participants were very enthusiastic, because in addition to the knowledge gained to be used as provision in the position of being a member of the Cooperative and becoming a provision in the position as a teacher or teaching staff at the Yogyakarta Cooperative Vocational School